Guidance on Growing Kaffir Lime Seedlings for Housewives at Pajagan Village, Sumedang - Budiarto, Rahmat; Mubarok, Syariful; Kusumiyati; Farida; Sutari, Wawan; Soleh, Mochamad Arief; Nuraini, Anne; Djaya, Luciana; Rasiska, Siska (Indonesian Journal of Community Services Cel, 2024)
Kaffir lime is popularly used by woman, especially housewives for cooking Indonesia dishes. The purpose of present activity was to provide simple guidance on growing kaffir lime for housewives at Pajagan Village, Sumedang, West Java. This counseling was provided for 20 housewives who are members of the Family Empowerment and Welfare (PKK) organization in Pajagan Village. The simple guidance is provided to housewives for planting kaffir lime in their yard, as follows: selecting best seedling, correct transplanting, regular irrigation, effective and efficient fertilizer application and proper harvesting. Housewives were each given one kaffir lime seedling to use as planting practice material. Housewives were very happy, grateful and believed to be more independent in terms of food spice. This activity is hoped to empower housewives to cultivate kaffir lime on their own yard for their daily spice needs.